Proceedings of the 10th International Symposium on Insect-Plant Relationships 1999
DOI: 10.1007/978-94-017-1890-5_19
|View full text |Cite
|
Sign up to set email alerts
|

Flowers in tri-trophic systems: mechanisms allowing selective exploitation by insect natural enemies for conservation biological control

Abstract: Many insects have coevolved with certain angiosperm taxa to act as pollinators. However, the nectar and pollen from such flowers is also widely fed upon by other insects, including entomophagous species. Conservation biological control seeks to maximise the impact of these natural enemies on crop pests by enhancing availability of nectar and pollen-rich plants in agroecosystems. A risk with this approach is that pests may also benefit from the food resource. We show that the flowers of some plants (viz., buckw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 9 publications
0
58
0
3
Order By: Relevance
“…Hyperparasitism or predation of parasitoids may be higher at close proximity to Xoral patches and may lead to signiWcantly higher mortality of foraging adult parasitoids (Rosenheim, 1998;Stephens et al, 1998). Provisioning of Xoral resources may also enhance pest Wtness (Irvin et al, 2006b;Baggen et al, 1999), in turn masking any eVect of Xoral resources on the natural-enemy population and herbivore population (Lavandero et al, 2006). Baggen et al (1999) demonstrated that 'selective resource subsidies' can beneWt parasitoids and not the target pest.…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperparasitism or predation of parasitoids may be higher at close proximity to Xoral patches and may lead to signiWcantly higher mortality of foraging adult parasitoids (Rosenheim, 1998;Stephens et al, 1998). Provisioning of Xoral resources may also enhance pest Wtness (Irvin et al, 2006b;Baggen et al, 1999), in turn masking any eVect of Xoral resources on the natural-enemy population and herbivore population (Lavandero et al, 2006). Baggen et al (1999) demonstrated that 'selective resource subsidies' can beneWt parasitoids and not the target pest.…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 99%
“…Provisioning of Xoral resources may also enhance pest Wtness (Irvin et al, 2006b;Baggen et al, 1999), in turn masking any eVect of Xoral resources on the natural-enemy population and herbivore population (Lavandero et al, 2006). Baggen et al (1999) demonstrated that 'selective resource subsidies' can beneWt parasitoids and not the target pest. Further research is required to evaluate whether potential plant candidates for G. ashmeadi enhancement may act as potential reservoirs for H. vitripennis or X. fastidiosa.…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 99%
“…This could lead to disillusionment among agricultural and horticultural practitioners with habitat restoration methods. In order for these methods to be effective, their implementation must be guided by empirical and theoretical research, such as the initial screening of individual tussock grass (Thomas et al 1991;MacLeod et al 2004) or flower species alone (Baggen et al 1999;Lavandero et al 2006) and then in mixtures (Pontin et al 2006; i.e. a directed approach sensu Gurr et al 2004).…”
Section: How Is Ecological Restoration Practised?mentioning
confidence: 99%
“…Parasitization performance of Trichogramma spp. (longevity, fecundity, adult emergence and female emergence) is known to be influenced by extrafloral nectar, pollen, honey, carbohydrate and protein (Ashley & Gonzalez, 1974;Hohmann et al, 1988;Baggen et al, 1999;Jervis et al, 2004;, Shearer & Atanassov, 2004Zhang et al, 2004;Wäckers, 2005;Witting-Bissinger, 2008).…”
Section: Introductionmentioning
confidence: 99%